Cardiac amyloidosis is not a single disease: a multiparametric comparison between the light chain and transthyretin forms. (3rd October 2022) - Neculae, G; Adam, R; Jercan, A; Badelita, S; Draghici, M; Stan, C; Rosca, M; Beladan, C; Coriu, D; Popescu, B A; Jurcut, R
Abstract: Background: Systemic amyloidoses represent a heterogeneous group of diseases resulting from the deposition of misfolded proteins as amyloid fibrils into the extracellular matrix of different organs. Based on this precursor protein, cardiac amyloidosis (CA) can be most frequently classified as: light chain (AL) and transthyretin (ATTR) amyloidosis, with different management and prognosis. Purpose: The purpose of this study is to establish a differential diagnosis algorithm targeted towards these two most frequent subtypes of CA. Although confirmation through invasive or non-invasive diagnostic algorithms is still mandatory for a final diagnosis, a series of clinical, paraclinical and imaging differences could possibly guide the choice for more complex diagnostic steps. Methods: We prospectively included all consecutive patients with ATTR and AL evaluated between 2018 and 2022 in our center. All patients had a complete clinical, paraclinical and imaging evaluation including myocardial deformation study, and confirmation of the final diagnosis, according to the current international recommendations. Results: The study population included 81 patients divided into 2 groups: ATTR (group 1, n=32: 30 variant and 2 wild type) and AL (group 2, n=49). ATTR patients were younger (50.7±13.9 vs. 60.2±7.3 years, p=0.0001), had predominantly more neurological symptoms, milder cardiac symptoms and lower values of cardiac biomarkers than AL: NT-proBNP (3095±4433 vs. 10382±9008 ng/ml, p=0.001) and high sensitive troponin I (0.0129±0.01 vs 0.177±0.2 ng/ml, p=0.0002), with better renal function (mean GFR 84.74±26.9 vs. 64.5±29.45 mL/min, p=0.003). We found no significant differences in terms of ECG changes. Moreover, at similar left ventricular (LV) wall thickness and ejection fraction, ATTR group had less pericardial effusions (53.6 vs. 86.8%, p=0.0027), better LV global longitudinal strain (−12.0±3.7 vs. −9.7±4.6%, p=0.03), RV strain (RVFW strain −19.7±6.2 vs. −14.5±11.0%, p=0.03) and also better reservoir and contractile function of the LA (LASr 17.2±12.3 vs. 11.2±7.4%, p=0.02). Based on this multiparametric comparison we proposed a prediction algorithm to differentiate between the 2 forms of CA. A score of equal or more than 4 from a maximum of 9 points, has been able to differentiate between AL and ATTR with a sensitivity and specificity of 78 and 80%, respectively; AUC= 0.82. Conclusions: CA is a complex entity and requires extensive testing through serum biomarkers, imaging, and invasive confirmation of amyloid infiltration in some cases. This study highlighted a series of non-invasive checkpoints, which can be useful in guiding the decision making process towards a more accurate and rapid differential diagnosis, in cases where a final diagnosis is crucial to be immediately established. Funding Acknowledgement: Type of funding sources: None.